Penutupan Diastema dengan Menggunakan Komposit Nanofiller - Rina Permatasari; Munyati Usman (Faculty of Dentistry, Universitas Indonesia, 2012)
The purpose of this work is to report a clinical care of diastema closure in case of multiple diastema using composite nanofiller material, as an alternative from orthodontic treatment and also porcelain crown restoration. This method proved to be conservative, practical, and provide high estethic value. DOI: 10.14693/jdi.v15i3.32